Stereotypical depiction of Erdheim-Chester Disease on Tc-99m MDP skeletal scintigraphy - Syeda Hadia Najam; Xain Tauqeer; Aamna Hassan; Kashif Siddique (Journal of the Pakistan Medical Association, 2025)
Erdheim-Chester Disease (ECD) is a rare systemic histiocytic disorder characterized by symmetrical skeletal involvement and variable visceral manifestations. Tc-99m MDP bone scintigraphy, CT, MRI, and FDG PET-CT are essential for diagnosis and disease mapping. ECD’s course depends on extraosseous involvement, with potential complications including heart and renal failure. We present the case of ECD with bilateral leg pain and orbital involvement. Imaging revealed mixed sclerotic and lytic skeletal lesions, cerebellar lesions, intraorbital soft tissue masses, mediastinal and retroperitoneal infiltration. Keywords: Erdheim-Chester Disease (ECD), Skeletal and Visceral Involvement, Tc-99m MDP Bone Scintigraphy